2019
DOI: 10.1186/s12962-019-0179-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of newborn pulse oximetry screening to detect critical congenital heart disease in Colombia

Abstract: Background In many countries, economic assessments of the routine use of pulse oximetry in the detection of Critical Congenital Heart Disease (CCHD) at birth has not yet been carried out. CCHDs necessarily require medical intervention within the first months of life. This assessment is a priority in low and medium resource countries. The purpose of this study was to assess the cost-effectiveness (CE) relation of pulse oximetry in the detection of cases of CCHD in Colombia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…After duplicate removals, 716 articles were considered eligible for screening by title and abstract. After full-text screening, 35 articles were included for the final assessment (see Appendix C for the PRISMA flow diagram) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No additional studies were found on the websites of the INAHTA HTA agencies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After duplicate removals, 716 articles were considered eligible for screening by title and abstract. After full-text screening, 35 articles were included for the final assessment (see Appendix C for the PRISMA flow diagram) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No additional studies were found on the websites of the INAHTA HTA agencies.…”
Section: Resultsmentioning
confidence: 99%
“…In some EEs, screening costs were estimated using a micro-costing approach. More specifically, they used a “time-and-motion” approach to derive cost estimates (tracking the time to perform the test and multiplying it by the value of average hourly compensation of the personnel involved) [ 39 , 47 , 49 , 53 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for establishing thresholds for costeffectiveness is driven by the fact that financial resources for healthcare systems are limited, and therefore, decisions on approval must balance out both value regarding health benefits and economic burden for the overall system (i.e., costs). Examples of cost-effectiveness analysis developed in the Colombian setting are presented in Londoño et al 2019 [21] and Aponte et al [22]. For wellknown international best modeling practices for costeffectiveness analysis, refer to ISPOR [23,24].…”
Section: Cost-effectiveness Analysis (Cea)mentioning
confidence: 99%
“…However, resultant potential treatment cost savings and quality of life improvements, which would have resulted in a full cost utility analysis, were rarely included in such studies. Likewise, many previous cost-effective ultrasound (US) studies were limited to reporting either the cost per detected CHD case (47)(48)(49) and/or to the diagnosis of a specific ailment, such as coarctation of the aorta (50). The cost per detected case was as high as $113,000 USD (at 2012 price levels) in the USA (48), with an antenatal ultrasound that includes five cardiac axial screening views having the lowest cost per detected case (51,52).…”
mentioning
confidence: 99%